Hubungan Antara Rinitis Alergi Dengan Kualitas Hidup Pada Mahasiswa Fakultas Kedokteran Universitas Bosowa Angkatan 2019-2022 - Thoriq, Andi Shohby; Hasbullah , Ayu Ameliyah; Suparman, Desi Dwirosalia Ningsih (Bosowa Medical Journal, 2024)
Inflammation of the nasal mucosa called allergic rhinitis is caused by an allergically sensitive reaction to certain allergens such as pollen, dust, tungsten, cigarette smoke, air pollution, and pet fur. Symptoms of allergic rhinitis include sneezing, a wet nose, itching, and clogging. Therefore, one reason why allergic rhinitis patients do not do physical activity. The aim of this research is to find out how the quality of life of students of the University of Bosowa Medical Faculty is affected by allergic rhinitis. Results of a study with 79 respondents. This quantitative research uses an observational analytical design and a cross-sectional approach. Spearman Rank Korean analysis, a type of non-parametric statistical test, is used to analyze data. The results of the study showed that as many as 32 students (40.5%) suffered from allergic rhinitis and 47 students (59.5%) did not suffer. To evaluate the quality of life of allergic rhinitis patients with the SF-36 Item (The Short Form 36 Items) filling instrument, as many as 30 students or 30.97% of allergic rinitis patients have a good quality of living. The results of data analysis using bivariate statistical tests showed a correlation of (R) 0.133 and a significance value of (P) 0.243 for the variable quality of life and allergic rhinitis. So, there's no link between allergic rhinitis and quality of life.